THE EFFECT OF SERVICE QUALITY, PROMOTION, AND PRICE ON CUSTOMER SATISFACTION OF GOJEK USERS - Astiti, Sonia Okky; Verawati, Dian Marlina; Novitaningtyas, Ivo (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
Transportation is one of the service sectors that has changed due to the development of internet technology. If initially there was only conventional transportation, now online-based transportation appears. As time goes by, more and more online transportation companies are struggling with one another to win the hearts of consumers. Customer satisfaction is one of the important factors that needs to be considered in running a business if you want to be sustainable. This study aims to determine the effect of service quality, promotion, and price on consumer satisfaction of Gojek users in Magelang. This study uses a quantitative approach by distributing questionnaires to 100 respondents as a sample based on the purposive sampling method. Questionnaires were distributed to 100 respondents who have used Gojek's online transportation services for at least the last 3 months and are domiciled in Magelang. The data that has been collected is then processed using the SPSS version 25 data processing application and analyzed using the Classical Assumption Test and Multiple Linear Regression Test. The results showed that service quality had a significant effect on consumer satisfaction, promotion had a significant effect on consumer satisfaction, and price was also significant on consumer satisfaction. Simultaneously, the variables of service quality, promotion, and price have a significant effect on consumer satisfaction of Gojek users in Magelang.